2018
DOI: 10.1029/2017tc004899
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics and Paleomagnetic Rotation Pattern of Yunnan (24°N–25°N, China): Gaoligong Fault Shear Versus Megablock Drift

Abstract: A wealth of paleomagnetic data from Yunnan (China) showed in the past a predominant post-Cretaceous clockwise (CW) rotation pattern, mostly explained invoking huge (hundreds of kilometer wide) blocks, laterally escaping (and/or rotating) due to India-Asia collision, separated by major strike-slip shear zones. Here we report on the paleomagnetism of the outcrops close to the Gaoligong dextral shear zone. Fifty paleomagnetic sites (503 samples) were sampled at variable distances (up to~25 km) from mylonites expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 158 publications
(341 reference statements)
2
30
1
1
Order By: Relevance
“…Considering an average 5 cm/year India‐Indochina convergence (Molnar & Tapponnier, ), and an oblique 40° subduction/collision from 32 to 15 Ma (thus assuming to have occurred mostly before the 20° CW Indochina rotation) translates into a ~550 km plate‐parallel dextral shear. This estimate is higher than the 230–290 km dextral displacement calculated by Pellegrino et al () for the Gaoligong fault on the basis of paleomagnetic data, implying that dextral shear parallel to the trench also occurred along other subparallel fault(s). After ~15 Ma, onset of southward crustal drift from Tibet changed the geodynamics of north Indochina, and dextral strain partitioning jumped farther west, along the Sagaing fault.…”
Section: Discussion: Crust Fragmentation Within the Simao And Lanpingcontrasting
confidence: 59%
See 4 more Smart Citations
“…Considering an average 5 cm/year India‐Indochina convergence (Molnar & Tapponnier, ), and an oblique 40° subduction/collision from 32 to 15 Ma (thus assuming to have occurred mostly before the 20° CW Indochina rotation) translates into a ~550 km plate‐parallel dextral shear. This estimate is higher than the 230–290 km dextral displacement calculated by Pellegrino et al () for the Gaoligong fault on the basis of paleomagnetic data, implying that dextral shear parallel to the trench also occurred along other subparallel fault(s). After ~15 Ma, onset of southward crustal drift from Tibet changed the geodynamics of north Indochina, and dextral strain partitioning jumped farther west, along the Sagaing fault.…”
Section: Discussion: Crust Fragmentation Within the Simao And Lanpingcontrasting
confidence: 59%
“…Such strike‐slip‐related crustal block rotations have been widely documented elsewhere (e.g., Beck, ; Hernandez‐Moreno et al, , ; Kimura et al, , ; Piper et al, ; Randall et al, ; Ron et al, ). Within north Indochina, Pellegrino et al () showed that crust east of the Gaoligong shear zone was broken in ≥1 km wide crustal blocks that experienced CW rotations of about 180° and that rotations ended at a ~20 km distance from the shear zone. They suggested that rotation pattern is consistent with a quasi‐continuous kinematic model (e.g., Sonder et al, ) and proposed a 230–290 km dextral offset for the Gaoligong shear zone based on rotation values and width of the block rotation zone.…”
Section: Discussion: Crust Fragmentation Within the Simao And Lanpingmentioning
confidence: 99%
See 3 more Smart Citations